Genetic variation of mitochondrial sequence-hv2 in Vietnamese populations - Hung, Do Manh; Ha, Nguyen Hai; Khoi, Pham Nhat; Nhung, Vu Phuong; Phong, Nguyen Van; Duong, Nguyen Thuy; Hai, Nong Van; Ton, Nguyen Dang (Academia Journal of Biology, 2016)
HV1 and HV2, which located in control D-loop region of mitochondrial, are the hyper-variable parts of mitochondrial DNA (mtDNA). Therefore, these two sequences were often used for evolutional and forensic science. In order to determine the genetic variation of populations belong to Nam-A and Nam-Dao language systems, we sequenced and analyzed the mtDNA HV2 region of individuals from four ethic groups: Kinh, Muong, Ede and Jarai which represent for those language systems. Study subjects are peripheral blood of 169 individuals belonging to four populations: Kinh, Muong, Ede and Jarai. HV2 regions were sequenced by Sanger sequencing. As a result, the analyzed mitochondrial control region sequences could be assigned to 79 different haplogroups, with the dominant proportion of three haplogroups: R, B and F. Donors representing Kinh or Muong population revealed higher haplogroup composition variation in comparison with those affiliated with Jarai or Ede. In addition, it was indicated that the 4 populations shared the genetic analogy with other populations inhabited in Southeast Asia and South Asia.